A multi-component domino bicyclization strategy: direct access to skeletally diverse quinazoline collection. Issue 36 (8th September 2016) - Jiang, Bo; Zhang, Tian-Shu; Fu, Rong; Hao, Wen-Juan; Wang, Shu-Liang; Tu, Shu-Jiang
Abstract: A multi-component bicyclization strategy has been established, allowing a flexible and practical approach to 29 examples of skeletally diverse fused quinazolines from low-cost and readily accessible aldehydes with cycloketones and cyanoamides. The reaction is easy to perform simply by mixing three common reactants and Cs2 CO3 in ethylene glycol under microwave irradiation and can be finished within 25 min with water as a sole byproduct. A sequence cascade process consisting of Knoevenagel condensation/[4+2] cyclization/intramolecular aza-Michael addition/aza-nucleophilic reaction-ring opening is involved in this new scaffold generating reaction. During this sequence, four stereogenic centers with one quaternary carbon-amino functionality have been controlled very well; and the stereochemistry has been unequivocally determined by X-ray structural analysis. Graphical abstract: